Iconographic Approach: A Study in Langkawit Strip Cartoon - Imelda Ann Achin; Oscar Gordon Wong; Addley Bromeo Bianus (Asian Scholars Network, 2022)
This research aims to analyze the function of images in linking current issues through Langkawit's cartoons. This study only focuses on studying two strip cartoons that contain images of animals drawn by Langkawit. This research uses the theory of Erwin Panofsky (1955) to understand the meaning of Langkawit's cartoon strips. This theory includes the level of pre-iconography, iconography analysis and iconological interpretation in assessing the diversity of animal imagery symbols expressed by Langkawit's strip cartoon. A semi-structured interview is conducted by interviewing Langkawit about the cartoon publication. Secondary data is obtained through printed materials such as library references, journals, theses, books, reports, newspapers and articles. This study found that the images of animals in strip cartoons have a symbolic function of giving or criticizing the social and political issues, as performed by Langkawit through his cartoons